Economic Considerations for Moving beyond the Kato-Katz Technique for Diagnosing Intestinal Parasites As We Move Towards Elimination - Turner,HC; Bettis,AA; Dunn,JC; Whitton,JM; Hollingsworth,D; Fleming,FM; Anderson,RM (TRENDS IN PARASITOLOGY, 2017)
While the need for more sensitive diagnostics for intestinal helminths is well known, the cost of developing and implementing new tests is considered relatively high compared to the Kato-Katz technique. Here, we review the reported costs of performing the Kato-Katz technique. We also outline several economic arguments we believe highlight the need for further investment in alternative diagnostics, and considerations that should be made when comparing their costs. In our opinion, we highlight that, without new diagnostic methods, it will be difficult for policy makers to make the most cost-effective decisions and that the potentially higher unit costs of new methods can be outweighed by the long-term programmatic benefits they have (such as the ability to detect the interruption of transmission).